Czynności procesowe stron w postępowaniu sądowoadministracyjnym - Malinowski, Piotr Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Explanation and understanding of the nature and function of the procedural acts as essential constituent elements forming the structure of the proceedings before the administrative court is fundamental to the scientific explanation of the procedural issues. Today, it is difficult to imagine a full study of any institution of procedural law without reference to the debate on the general assumptions resulting from the nature, function and properties of procedural acts. Consequently, procedural acts in administrative court proceedings are to be counted as the most important phenomena of the process, and the very concept of a procedural step to basic research equipment of the proceedings before the administrative court, without which it is difficult to properly introduce and explain the institutions of this procedure.Procedural acts, extracted from a wider range of procedural facts, build the structures in the proceedings before the administrative court. These are the elements of a process that dynamize the process. Procedural acts lead to the initiation, development and implementation of the main purpose of the procedure, which is the judgment of the court deciding a dispute over the legality of the action, inaction or chronic proceedings by a public authority.In the proceedings before the administrative court the procedural acts of the parties should be analyzed in conjunction with the construction of the capacity to bring an action before the court. Differentiation of the capacity to bring an action before the court because of the type of protected interest is important from the point of view of reflection on the specific features of procedural acts of the parties that show some differences, depending on whether the party to the proceedings is an entity acting in the interests of the individual, public or social.
Keywords: czynność procesowa; strona; proces prawny; sąd; administracja; charakter fakultatywny; odwołalność